2013
DOI: 10.1080/08946566.2012.751831
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological Correlates of Performance Based Functional Status in Elder Adult Protective Services Referrals for Capacity Assessments

Abstract: We have previously described high rates of executive function impairment in clients referred by Adult Protective Services (APS) to geriatric psychiatry for decision-making capacity assessments. The purpose of this study was to determine the independent relationship between neuropsychological screening instruments, particularly instruments sensitive to executive function, and performance-based functional tasks in elder referrals. Our retrospective medical review (n = 75/157 referrals completed all neuropsycholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Executive function measures have consistently been shown to correlate well with functional status (Johnson, Lui, & Yaffe, 2007). We have previously shown that executive function was the best predictor of elder APS clients' abilities to demonstrate how to read a bill, write a check, read a check register, use a check register, state what number to call in an emergency, and demonstrate how to use a telephone book (Schillerstrom, et al, 2013). Thus, APS clients with impaired executive processes may be unable to take advantage of as-needed or selfinitiated interventions and may need more restrictive oversight, such as daily provider services, home health management, or perhaps even guardianship to prevent recurrence of exploitation or neglect.…”
Section: Resultsmentioning
confidence: 97%
“…Executive function measures have consistently been shown to correlate well with functional status (Johnson, Lui, & Yaffe, 2007). We have previously shown that executive function was the best predictor of elder APS clients' abilities to demonstrate how to read a bill, write a check, read a check register, use a check register, state what number to call in an emergency, and demonstrate how to use a telephone book (Schillerstrom, et al, 2013). Thus, APS clients with impaired executive processes may be unable to take advantage of as-needed or selfinitiated interventions and may need more restrictive oversight, such as daily provider services, home health management, or perhaps even guardianship to prevent recurrence of exploitation or neglect.…”
Section: Resultsmentioning
confidence: 97%
“…This includes the MacArthur Structured Assessment of Competencies of Criminal Defendants (MacSAC-CD), which was validated for schizophrenia and affective disorders (26), and the MacCAT-T, which was validated for schizophrenia and schizoaffective disorder (27). Similarly, up to this point impairment in executive function seems to be the most significant cognitive predictor of inability to obtain the standards required to maintain independence in decision-making (10,28). However, as demonstrated in the above cases, patients with severe personality disorders sufficient to impair decision-making do not necessarily have clinically significant executive function deficits and generally perform very well on global cognitive assessments.…”
Section: Discussionmentioning
confidence: 99%
“…This brings us back to the original concept for presenting these cases: Are patients with personality disorders substantially unable to care for themselves and manage their own lives, or are they better characterized as substantially unwilling ? If we refer to the data showing that executive function correlates reasonably with capacity and self‐care , then two paths are possible. The first way of interpreting this is to posit that the above clients are simply unwilling to provide adequate care for themselves, but theoretically they could perform appropriately since they are generally cognitively intact.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Executive functioning (EF) is an umbrella term composed of complex and multidimensional processes such as working memory and mental flexibility, initiation and maintenance of behavior, inhibition and response selection, and meta-tasking (MT) (Suchy, 2015). EF has consistently been linked to requisite skills for independent living (Jefferson, Paul, Ozonoff, & Cohen, 2006;Marshall et al, 2011;Uemura, Yamada, Nagai, & Ichihashi, 2011), including financial management (Nakhla, 2019;Schillerstrom et al, 2013), medication or medical regimen management (Manning, Clarke, Lorry, Weintraub, Wilkinson, Duda, & Moberg, 2012;Stoer et al, 2008;Suchy et al, 2016;Suchy et al, 2020;Ziemnik & Suchy, 2019), driving (Brown et al, 2016;Hayashi, Rivera, Modico, Foreman, & Wirth, 2017;P-ope, Bell, & Stavrinos, 2017), and meal preparation (Craik & Bialystok, 2006;Jefferson, Paul, Ozonoff, & Cohen, 2006;Kosowicz & MacPherson, 2017).…”
mentioning
confidence: 99%